Psychological Issues Affecting Senior High School Students' Development in English-speaking Proficiency: A Case Study - Hreesang Satria Bagaskara (Universitas Negeri Surabaya, 2024)
This research aims to investigate psychological issues students encounter in developing their English-speaking proficiency and what strategies they use to overcome those issues. This study was conducted in a high school in Surabaya, Indonesia. It was bottom-lined from a case study where the researcher conducted a teaching practicum, the students were complaining when being asked to speak English. Semi-structured interviews for nine participants were applied to collect the data, and it was analyzed using thematic analysis. The finding shows that participants encountered fear of making mistakes, fear of mispronouncing words, fear of language structures, fear of public speaking, fear of being made fun of, lack of confidence, doubtfulness, low motivation, nervousness, insecurity, and annoyance of negative evaluation. It also finds that participants use preparation, positive-thinking, and peer-seeking strategies out of the others (e.g., relaxation, preparation, positive-thinking, peer-seeking, and resignation) to overcome the issues.